Repository policies in four higher education libraries in Surabaya, East Java - Zuntriana, Ari; Anesti, Dian; Mufid, Mufid (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This research examines the electronic theses and dissertation repository policies at four universities in Surabaya, namely UIN Sunan Ampel, Universitas Airlangga, Institut Teknologi Sepuluh Nopember, and Universitas Kristen Petra. It explores the policy formulation process and evaluates whether the existing policies have considered good repository governance practices, such as data protection, notice and take-down policy, and data reuse. Data Collection Methods. This study employs a descriptive qualitative approach, using interviews, policy documents, and writing guidelines as primary data sources. Data analysis. Data was analyzed using the Miles and Huberman interactive analysis model, which consists of data collection, data reduction, data display, and conclusion. Results and Discussion. The policy formulation process follows a top-down approach involving university rectors/vice rectors, library heads, and librarians. The top managements determine the publication model and embargo periods. However, repository policies remain incomplete, with some still verbally communicated rather than properly documented. Conclusion. Repository policies are still heavily influenced by university leaders, so the focus is currently on access restrictions and embargoes to increase the number of publications, rather than improving governance. The role of librarians in raising awareness and advocating for open access is necessary.